2023
DOI: 10.1039/d3cp01160g
|View full text |Cite
|
Sign up to set email alerts
|

Resistive switching and role of interfaces in memristive devices based on amorphous NbOx grown by anodic oxidation

Abstract: Memristive devices based on the resistive switching mechanism are continuously attracting attention in the framework of neuromorphic computing and next-generation memories. Here, we report on a comprehensive analysis of resistive...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 59 publications
(118 reference statements)
2
3
0
Order By: Relevance
“…1 a in which it can be appreciated the compactness of the NbO x layer and the smoothness of the BE interface due to the anodic oxidation process, as confirmed also by Transmission Electron Microscopy (TEM) analysis reported in our previous work 25 . Note that a detailed chemical and structural analysis revealed that the NbO x is amorphous and is characterised by the presence of Nb(+ 5) oxidation state on the top of the anodized film and Nb(+ 2) oxidation state at the interface with the common Nb BE, as investigated in our previous work 25 . Note that while the same oxidation states are then found after the deposition with the Au TE 25 , chemical properties at the metal/NbO x interface with the TE may locally slightly vary the oxide stoichiometry due to the interaction with the TE metal.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…1 a in which it can be appreciated the compactness of the NbO x layer and the smoothness of the BE interface due to the anodic oxidation process, as confirmed also by Transmission Electron Microscopy (TEM) analysis reported in our previous work 25 . Note that a detailed chemical and structural analysis revealed that the NbO x is amorphous and is characterised by the presence of Nb(+ 5) oxidation state on the top of the anodized film and Nb(+ 2) oxidation state at the interface with the common Nb BE, as investigated in our previous work 25 . Note that while the same oxidation states are then found after the deposition with the Au TE 25 , chemical properties at the metal/NbO x interface with the TE may locally slightly vary the oxide stoichiometry due to the interaction with the TE metal.…”
Section: Resultssupporting
confidence: 79%
“…An example of the cross-section of the device structure can be found in Fig. 1 a in which it can be appreciated the compactness of the NbO x layer and the smoothness of the BE interface due to the anodic oxidation process, as confirmed also by Transmission Electron Microscopy (TEM) analysis reported in our previous work 25 . Note that a detailed chemical and structural analysis revealed that the NbO x is amorphous and is characterised by the presence of Nb(+ 5) oxidation state on the top of the anodized film and Nb(+ 2) oxidation state at the interface with the common Nb BE, as investigated in our previous work 25 .…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations